Can social risks in early life predict children's health and academic outcomes? An analysis of the Longitudinal Study of Australian Children. (March 2022) - Walls, Alexandra; Boyd, Mark; McMichael, Gai; Smithers, Lisa G.
Abstract: Exposure to social risk in early life negatively impacts the health and wellbeing of children. While screening for social determinants of health is recommended, there is little evidence that identifying social risk early in life predicts longer-term poorer outcomes. The purpose of this study is to examine the extent to which assessing social risk using a standardized tool in young children up to age 6 years might predict poor health and academic performance at 10–11 years old. The social risk domains studied were housing instability, food insecurity, financial strain, transport problems, safety, lack of support and unemployment. The predictive validity of these social risk domains measured at 0–5 years was examined using data from the Longitudinal Study of Australian Children. Outcomes at 10–11 years included ongoing diseases and mental health conditions, hospitalization, injury, dental problems, overweight or obesity and academic achievement. Financial strain and inability to access support were the most sensitive measures of poor outcomes. Across all social risks, the positive predictive value was highest for academic outcomes. Across all domains, there was higher sensitivity for children with 2 or more social risks. Items in the social risk screening tool were moderate predictors of academic outcomes, but weak predictors of health outcomes at 10–11 years. This data will be useful for informing screening for social determinants of health. Highlights: Social risks from 0 to 5 y were moderate predictors of 8-year-old school assessments. Financial strain and a lack of social support had modest sensitivity. Sensitivity is increased by applying a threshold of 2 or more social risks. The positive predictive value of social needs was highest for academic outcomes.